Return on equity bca syariah 2020–2024: suatu kajian kritik finansial terhadap efisiensi, pertumbuhan ekuitas, dan manajemen risiko - Muawanah, Nurul (Maliki Interdisciplinary Journal, 2025)
This study evaluates the Return on Equity (ROE) performance of PT Bank BCA Syariah over 2020–2024 from a financial critique perspective. Using secondary data from BCAS annual reports and empirical literature on profitability determinants in Islamic banking, the paper disentangles contributions from operational efficiency, equity dynamics, and asset quality to ROE changes. ROE rose from 3.1% to 5.9% over the period; the rise was driven by net income growth and improved cost efficiency, while very low NPF reduced provisioning needs. A critical reading cautions that ROE interpretation must account for denominator effects (equity growth) and risk-management strategies. The paper recommends comparative studies and use of complementary metrics to assess profit sustainability.